Dead Ends and Detours Towards a Rigid Hexasalicylic Aldehyde Precursor for Triptycene‐Based Porous Materials - Dennis Reinhard; Sven M. Elbert; Wen‐Shan Zhang; Frank Rominger; Rasmus R. Schröder; Michael Mastalerz (ChemistryEurope)
Abstract The synthesis of a rigid hexakis(salicylaldehyde) precursor for porous organic metal salphens based on triptycene is presented. Synthetic approaches, their failures and how to learn from these to circumvent those and finally reach the synthetic goal is discussed. First tests to convert this new rigid building block into organic molecules of intrinsic microporsity (OMIM) by making a hexakis nickelsalphen complex as well as a metal‐assisted salphen organic framework (MaSOF) are presented. Their properties as porous materials have been studied and compared to materials based on similar but more flexible building blocks.